APPLICATION OF THE AUTOMATIC CONTROL THEORY FOR SEARCHING RATIONAL WAYS OF TECHNICAL DIAGNOSTICS AND IMPROVEMENT OF TECHNICAL CHARACTERISTICS OF 2E36 STABILISER - Kasimov, Anatoliy; Shpinda, Yevhen; Horbov, Oleksii; Kovtunov, Yurii; Kolobov, Igor; Krasnoshapka, Yuri (Сучасні інформаційні системи, 2019)
The subject matter of the article is the process of troubleshooting a BMP-2 fire control system The goal of the study is the developing a fault finding algorithm in this system and to offer suggestions for improving the technical characteristics of the weapon stabilizer based on the analysis of design and circuit solutions and technical characteristics of the BMP-2 fire control system. The tasks to be solved are: to conduct an analysis of the BMP-2 fire control system as a closed automatic control system provide suggestions for improving the performance of the stabilizer; to draw up a block diagram of a rational technical diagnostics of the 2E36 stabilizer and to propose a method for troubleshooting.General scientific and special methods of scientific knowledge are used. The following results are obtained. It is proposed to improve the technical characteristics of the 2E36 stabilizer by reducing the number of gyrotachometers from four to two with a parallel increase in the remaining signal branching, as well as improving the speed characteristics by installing an additional power source - a capacitor battery, for short-term and short-term engines. A rational technical diagnostics block scheme of the 2E36 stabilizer has been drawn up and methods of troubleshooting in the form of rigidity tuning cards, damping and vibration of the gun and turret stabilizer have been proposed. The diagnostic methods of elemental and group inspections are analyzed. Based on the analysis, the basic algorithms for the diagnostic process of tower and gun stabilization were developed. Thanks to this in the area of the task, personnel and repair units will be able to ensure the combat readiness of the equipment as quickly as possible. Conclusions. Gun stabilizers and turrets are closed automatic control systems based on the principle of adjusting the deviation of the adjustable value from a predetermined value. The objects of regulation in these stabilization systems are the cannon and the tower, and the adjustable values are their angular velocities. Feedback optimization involves reducing the number of gyro tachometers from four to two, which will increase the power reserve and give more opportunities for further stabilizer upgrades. Acceleration of the accelerator of the executive motor can be accomplished by installing a capacitor battery. The most long-term step in the process of repairing the complexity of complex systems is the process of finding failed items. The scheme of rational technical diagnostics provides the basic algorithms for carrying out the diagnostic process of stabilization of the tower and the gun, which allows to search for problems with maximum efficiency.